RUSSIA IN TRANSFORMATIONAL PROCESSES OF MODERNITY: CULTURAL ASPECT - Aleksey N. Tarasov (Russian Studies in Culture and Society)
The article analyzes the cultural aspect of the ongoing geopolitical transformation in the world, as well as the impact of these processes on Russia.